Intensi Whistleblowing Auditor: Peran Perlindungan Hukum sebagai Variabel Moderasi - anggi chandraini; Rindu Rika Gamayumi; Erna Listyaningsih (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: The purpose of this research is to examine the factors that influence the auditor's intention to report fraud. Research methodology: Researchers collected primary data through questionnaires using google form media which were filled in by 74 KAP auditors in Palembang and Bandar Lampung. The data was tested using the Partial Least Square (PLS) version 3.0 application. Results: The results of the study show that the influence of organizational commitment, professional commitment, moral intensity, personal cost, locus of control, and rewards all positively affect whistleblowing intention. However, there is no evidence that the seriousness of the fraud has any effect. The legal protection variable has not been proven capable of moderating or strengthening the relationship between organizational commitment, seriousness of fraud, and professional commitment to whistleblowing intentions. Legal protection has been proven to strengthen the relationship between moral intensity, personal cost, locus of control, and reward on whistleblowing intention. Limitations: Researcher Tunable to approach respondents directly and the number of samples was relatively small because the auditors at the public accounting firm under study were quite busy. Contribution: This research contributes to the Public Accounting Firm, the KAP must provide legal protection for auditors who dare to do whistleblowing in order to get a good image of the public accounting profession in the eyes of the wider community.